Attitudes Toward Climate Change: Major Emitters in Southwestern Kansas - Harrington, Lisa M.B. (My University, 2010)
As part of an initiative to improve understanding of place-to-place differences in greenhouse gas emissions, local changes in radiative forcing, and mitigative potential, the attitudes of decision- makers in the major greenhouse-gas-emitting industries in a 6-county study area in southwestern Kansas were investigated. This study included both mailed questionnaire and unstructured interview techniques, with quantitative and qualitative components. The information obtained from one method tended to corroborate data obtained from the other. Results indicate that, in this area, many respondents in the best positions to take mitigative actions are unconvinced of human-induced climate change. There are some variations among industries, with those involved in natural gas or electricity provision least convinced of potential negative impacts related to greenhouse gas emissions/ climate change. In this region, it would appear that better communication of ‘proof’ of human climate impacts, as well as mitigative opportunities, would be a necessary part of encouraging industries to take action.
Keywords: Attitudes; Climate change; Mitigation; Local places; Global warming; Kansas